Implementasi Pendidikan Multikultural dengan Model Kepemimpinan Demokratis Kepala Sekolah Menengah Atas Katolik St. Petrus Kanisius Palangka Raya - Syahmidi, Syahmidi (LP2M IAIN Palangka Raya, 2014)
In Catholic High School St. Peter Canisius Palangka Raya, researchers noticed something interesting. Researchers looked learners mingling, playing, joking, eating, and conduct joint activities. They look like forget where they came from, what color their skin, how the social status of their families. It is also the issue of religion, as long as they do not interfere with other religions, they still carry out activities together with not differentiate each other. Similarly, the teachers and staff at the school, they hang out and work without any sense of distinction. Formulation of the problem in this paper is how the Headmaster of Catholic High School St. Peter Canisius Palangka Raya in multicultural perspective, how the implementation of multicultural education at Catholic High School St. Peter Canisius Palangka Raya and any supporting aspects in the implementation of multicultural education at Catholic High School St. Peter Canisius Palangka Raya.This research is kind of field research. Including in descriptive research with case study strategy. Type of this case study is a